Incipient speciation revealed in Anastrepha fraterculus (Diptera; Tephritidae) by studies on mating compatibility, sex pheromones, hybridization, and cytology - Cáceres, Carlos (2009)
It has long been proposed that the nominal species Anastrepha fraterculus is a species complex and earlier studies showed high levels of pre-zygotic isolation between two laboratory strains from Argentina and Peru. Further experiments were carried out on the same populations and on their reciprocal hybrids, including pre- and post-zygotic isolation studies, pheromone analysis, and mitotic and polytene chromosome analysis. A high level of pre-zygotic isolation had been maintained between the parental strains despite 3 years of laboratory rearing under identical conditions. The level of pre-zygotic isolation was reduced in matings with hybrids. There were also differences in other components of mating behaviour. There were quantitative and qualitative differences in the sex pheromone of the two strains with the hybrids producing a mixture. The pre-zygotic isolation barriers were complemented by high levels of post-zygotic inviability and sex ratio distortion, most likely not due to Wolbachia, although there was evidence of some cytoplasmic factor involved in sex ratio distortion. Analysis of polytene chromosomes revealed a high level of asynapsis in the hybrids, together with karyotypic differences between the parental strains. The combined results of the present study indicate that these two strains belong to different biological entities within the proposed A. fraterculus complex.